In Vitro Biosynthesis of Ag, Au and Te-Containing Nanostructures by Exiguobacterium Cell-Free Extracts - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Rios-Silva, M (BioMed Central Ltd., 2020)
Background: The bacterial genus Exiguobacterium includes several species that inhabit environments with a wide range of temperature, salinity, and pH. This is why the microorganisms from this genus are known generically as polyextremophiles. Several environmental isolates have been explored and characterized for enzyme production as well as for bioremediation purposes. In this line, toxic metal(loid) reduction by these microorganisms represents an approach to decontaminate soluble metal ions via their transformation into less toxic, insoluble derivatives. Microbial-mediated metal(loid) reduction frequently results in the synthesis of nanoscale structures - nanostructures (NS) -. Thus, microorganisms could be used as an ecofriendly way to get NS. Results: We analyzed the tolerance of Exiguobacterium acetylicum MF03, E. aurantiacum MF06, and E. profundum MF08 to Silver (I), gold (III), and tellurium (IV) compounds. Specifically, we explored the ability of cell-free extracts from these bacteria to reduce these toxicants and synthesize NS in vitro, both in the presence or absence of oxygen. All isolates exhibited higher tolerance to these toxicants in anaerobiosis. While in the absence of oxygen they showed high tellurite- and silver-reducing activity at pH 9.0, whereas AuCl4- which was reduced at pH 7.0 in both conditions. Given these results, cell-free extracts were used to synthesize NS containing silver, gold or tellurium, characterizing their size, morphology and chemical composition. Silver and tellurium NS exhibited smaller size under anaerobiosis and their morphology was circular (silver NS), starred (tellurium NS) or amorphous (gold NS). Conclusions: This nanostructure-synthesizing ability makes these isolates interesting candidates to get NS with biotechnological potential. © 2020 The Author(s).